Justice In Management, Utilization and Preservation of Local Plant Varieties - Yuliana Diah Warsiki Susi Irianti (Master of Law Program, Ekasakti University, 2024)
Justice is important (urgent) in the Management, Utilization and Conservation of Local Plant Varieties and as an effort to realize the protection of the rights of local communities. Justice in question must be a basic value that must be realized through law, in this case the Plant Variety Protection Law, article 7, and Regional Regulations. Substantially, both laws and regional regulations must accommodate all stakeholders' interests and needs in the management, utilization and preservation of local plant varieties.